Sensitivity, hedonics and preferences for basic tastes and fat amongst adults and children of differing weight status: A comprehensive review. (March 2016) - Cox, David N.; Hendrie, Gilly A.; Carty, Danika
Highlights: Review of taste sensitivity, hedonics and preference relationships to weight. Suggestive negative association between fat taste sensitivity and weight status. Weak evidence for association between sweet, salty, sour or bitter tastes and weight. Some evidence for fat hedonics and fat preference and increased weight status. In children, suggestive positive relationship between salt, intake and weight. Abstract: It is likely that variation in individual responsiveness to taste stimuli plays a pivotal role in food choice, however the importance of this role in relation to weight status is not yet known. This comprehensive review sought to determine if sensitivity, hedonics, and preference for the basic tastes and fat characteristics of food differs between normal and overweight/obese individuals. We identified 25 human studies (1980–2013) that sought to measure one or more variables' relationship to weight status. There is no clear evidence of a negative association between fat taste sensitivity and weight status, and little evidence of a relationship between sweet, salty, sour or bitter tastes and weight status. There was some evidence for an association for fat hedonics and a preference for fat and increased weight status. Amongst children there was suggestive evidence for a positive relationship between salt, dietary intake and weight status. There is a need to clearly define and adopt a hypothesis-led approach, using more rigorous measures of sensory characterisation and dietary intake to better understand whether the sensory characteristics of diet influence food choices and weight status.